KERAGAMAN SUARA KODOK PURU BESAR Phrynoidis aspera (Gravenhorst, 1829) ASAL JAWA BARAT - Hellen Kurniati (Research Center for Biology-Indonesian Institute of Sciences, 2013)
Giant River Toad Phrynoidis aspera (Gravenhorst, 1829) is a largest generalist toad that is able to adapt to a variety of habitats and elevations. The complete calls of Giant River Toad had not been published before. To know all of sound characters of the toad, a total of five individuals males P. aspera vocalization were recorded on 30 October 2010 (1 individual; air temperature: 23.1°C; water temperature: 18.1°C) by using an Audio Technica AT875R microphone, the sound was recorded on a Fostex FR 2LE in WAV format; and on 22-24 September 2011 (4 individuals; air temperature 21.0°C-23.4°C; water temperature 21.6°C-22.0°C) in Curug Nangka, Mount Salak foot hill,West Java by using PCM-M10 Sony Recorder. The toad has four types of call: (1) Call type 1, consists of impulses without harmonic and average band width is 317.44 Hertz and average of amplitude is 40.43; (2) Call type 2, consists of pure tone with many sub-harmonics, average range frequency is 1420.28 Hertz and average of amplitude is 42.67; (3) Call type 3, consists of impulses and pure tone with two weak harmonics and average band width is 373.81 Hertz and average of amplitude is 48.19; (4) Call type 4, consists of impulses without harmonic and average band width is 792.62 Hertz and average of amplitude is 51.01. Based on the number of calls that were recorded of five individuals from the Mount Salak foot hill, call type 4 is its major call (common advertisement call), but the three others call types are minor calls.